Time-fractional telegraph equation of distributed order in higher dimensions - Vieira, N. (2021)
In this work, the Cauchy problem for the time-fractional telegraph equation of distributed order in $\BR^n × \BR^+$ is considered. By employing the technique of the Fourier, Laplace and Mellin transforms, a representation of the fundamental solution of this equation in terms of convolutions involving the Fox H-function is obtained. Some particular choices of the density functions in the form of elementary functions are studied. Fractional moments of the fundamental solution are computed in the Laplace domain. Finally, by application of the Tauberian theorems, we study the asymptotic behaviour of the second-order moment (variance) in the time domain.